Social Networking of Privacy - Žunić-Pavlović, Vesna; Kovačević-Lepojević, Marina; Lepojević, Borko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
Since the late nineties, when there was a revival of the multiplier concept of social networking on the Internet, public attention has focused on the study of the negative aspects of the functioning of social networking sites, especially complaints relating to abuse of privacy. The results of the research on the routine activities of social networking site users show that more than half of users share their personal information. On the other hand, the safety platforms of social networking sites are weak. A particular problem is the unauthorized collection of data on citizens' communications by the security agencies of the developed countries of the world as part of the activities related to the prevention of terrorism and crime. The aim of this article is to assess the negative consequences of social networking in the context of privacy issues. Besides the review of the international and domestic laws on social networking sites, some safety instructions for users and social networking sites will be given.